81 More than just keeping busy: the protective effects of organised activity participation on substance use and violent behaviour among urban youth. (19th September 2017) - Eisman, Andria; Lee, Daniel; Stoddard, Sarah; Zimmerman, Marc
Abstract : Background: Violence and substance use disproportionately affect African-American youth in urban, disadvantaged communities. Strength-based approaches to ameliorating risk, such as organised activity participation, are promising. Researchers suggest that fostering prosocial peers and non-familial adult relationships is a mechanism by which organised activities reduce the risk of substance use and violence. Yet, few researchers have examined explicitly this mechanism.Â Methods: We used a parallel mediation model, an aspect of the SEM framework, to assess whether organised activity participation decreases substance use and violence over time through prosocial peers and adults. We examined these relationships among a school-based sample of youth from an urban, economically disadvantaged community (Wave 1: n=681; 50% female; Mage=14.86 years; SD=0.65). Results: We found significant indirect effects from organised activities to cigarette use (b=0.03), and violent behaviour (b=0.02) through prosocial peer relationships, but not prosocial adults. We did not find significant indirect effects linking organised activities to alcohol use. Conclusions: Our results suggest that organised activities may help youth expand prosocial peer relationships, which, in turn, reduces risk for substance use and violence. To this end, the efficacy of prevention efforts may be enhanced if programs help youths cultivate prosocial relationships with peers. In contrast to previous research, prosocial adults did not mediate the link between organised activity participation and substance use and violent behaviour. Implications for prevention are discussed.